Latent profiles of psychological empowerment in Chinese police officers: links to emotional support and work well-being - Tian, Yuan; Jia, Zhe; Li, Na; Wu, Yunpeng; Deng, Jue; Tang, Ya’nan; Huang, Jinshu; Xu, Xizheng (Frontiers in Psychology, 2026)
IntroductionPsychological empowerment is a critical factor for employee work well-being, particularly within high-stress professions such as policing. However, experiences of empowerment among individuals are not uniform. This study aims to identify distinct profiles of psychological empowerment among police officers and to examine their associations with perceived coworker support and work well-being.MethodsA person-centered approach was adopted. Data were collected from 505 Chinese police officers. Latent Profile Analysis (LPA) was employed to identify subgroups based on their psychological empowerment patterns.ResultsThe analysis revealed two distinct profiles: a “Globally Disempowered” profile and a “Globally Empowered” profile. Perceived emotional support from coworkers was a significant predictor of profile membership, where higher levels of support increased the likelihood of belonging to the empowered group. Furthermore, officers in the high empowerment profile reported significantly greater work well-being compared to those in the low empowerment profile.DiscussionThe findings underscore the heterogeneity in psychological empowerment experiences within the policing context. They emphasize the pivotal role of fostering emotional peer support as a means to enhance officers’ psychological empowerment and, consequently, their work well-being. Practical implications for organizational interventions are discussed.